IN VIVO EVALUATION OF MISOPROSTOL FLOATING MICROSPHERES - Kondi Vanitha; Mohan Varma; Allure Ramesh (Indonesian Journal of Pharmacy, 2012)
Prostaglandin  (PG)  has  been  reported  to  be  an  important protective  and  acid  suppressive  factor  in  the  gastric  mucosa.  The objective  of  the  study  was  to  develop  and  evaluate  a  stomach specific  drug  delivery  system  for  controlled  release  of  Misoprostal  a PE analogue for gastric ulcer induced NSAIDs. Floating microspheres were  prepared  by  emulsification-solvent  evaporation  method  using ethyl  cellulose  as  a  polymer,  carbopol  as  mucoadhesive  polymer. Ulcers were induced by the oral administration of absolute ethanol (5 mL/kg)  to  24  h  fasted  Wistar  male  rats  (n=8),  weighing  200  g. Sodium  bicarbonate  solution,  misoprostal  solution  and  drug  loaded microspheres were tested. Formulations were administered orally 1h before the administration of ethanol. Prior to the oral administration, rats  were  anesthetized  with  ethylic  ether.  After  2  h  of  ethanol administration,  animals  were  sacrificed;  the  stomachs  were removed,  opened  along  he  greater  curvature  and  examined  for lesion measurements. Ulcer indexes (UI) were calculated. The in vivo evaluation showed that ulcer  index values were 0.61 ± 0.14 for the sodium  bicarbonate  solution,  0.58  ±0.18  for  the  misoprostal  and 0.11  ±  0.06  for  the  misoprostal-loaded  microspheres.  The  KruskalWallis  test  detected  statistical  differences  (p  =0.002)  between  the ulcer  indexes.  The  multiple  analyses  (Student-Newman-Keuls) showed  that  the  misoprostal  loaded  microspheres  presented  a gastric  ulcer  index  statistically  lower  than  that  of  the  sodium bicarbonate  solution  (p  =  0.001)  and  the  misoprostal  solution  (p  = 0.021).  The  percentages  of  ulceration  inhibition  were  31  and  75% after  the  administration  of  misoprostal  solution  and  microspheres, respectively.  In  conclusion,  the  in  vivo  evaluation  showed  that  the microspheres  presented  ulcer  index  lower  than  the  solutions, showing  that  misoprostal-loaded  microspheres  were  efficient  in protecting the stomach against ulcer formation.Key words: Misoprostal, microspheres, ulcer index,